Exploring Medical Resources of Permanent Supportive Housing Programs in the West Side of Chicago - Rani, Sneha; Bhattacharya, Deeya; Rogers, Christina; Fitzpatrick, Quinn; Kunta, Charita; Robertson, Kyle A.; Olison, Eugenia; Chandler, Elizabeth (International Journal on Homelessness, 2026)
Objective: The purpose of this study is to examine how permanent supportive housing (PSH) programs in Chicago’s West Side integrate and deliver medical services across single-site, scattered-site, and hybrid models. Rather than measuring resident outcomes directly, this study presents a structured assessment of how PSH organizations operationalize healthcare delivery, funding, and coordination within their housing programs.Methods: We conducted a qualitative descriptive study using structured virtual interviews with 18 representatives from six PSH organizations on Chicago’s West Side representing single-site, scattered-site, and hybrid models. Each interview consisted of a member of the research team and one to three members of the PSH organization. Interviews examined organizational operations, healthcare delivery, resident engagement, and barriers to care. Since the sample size was small, the data were analyzed descriptively to identify common themes in implementation, funding, and access. The Rush University Institutional Review Board reviewed the study and determined it exempt as it did not involve human subjects or identifiable resident data and because representatives from the organizations were to be interviewed and not the residents themselves.Results: Of the six organizations interviewed, two operated single-site programs, two operated scattered-site programs and two employed hybrid models, with medical services for residents either provided on-site or referred to external providers, or a combination of both. Partnerships between organizations and outside healthcare providers or pharmacies, in addition to insurance coverage and funding (e.g. Medicaid, grants) affect access to healthcare. The intersection of organizational constraints and resident-level barriers, such as lack of transportation, often compounds challenges to healthcare delivery. Health services used by residents also varied between organizations, though mental health services were consistently reported as the most frequently utilized by residents. Organizations offering on-site healthcare noted positive long-term health impacts on their residents, suggesting that centralization of their healthcare may foster continuity of care even after housing stabilization. In contrast, although scattered-site models may offer more freedom and additional specialty services, these models often fragment healthcare and depend heavily upon residents' ability, access, and initiative.Conclusions: This study found that both single- and scattered-site models had distinct advantages and challenges, but that hybrid models allow for maximum medical benefit to residents. Ultimately, the determining factors in the successful operation of PSH models are adequate funding and structural barriers within policymaking.